Screening of Heavy Metals in Selected Vegetables using the Papain Inhibitive Assay (Asian Journal of Plant Biology, 2014)
Vegetables are major source of heavy metals contaminant in the diet of humans. Currently,monitoring of heavy metals in vegetables is carried out by instruments such as Inductively-Coupled Plasma Optical Emission Spectrophotometer (ICP-OES) or Flow Injection MercurySystem (FIMS). Instrumental method alone is costly, need skilled personnel and timeconsuming. In this work, the papain assay was used to screen for the presence of heavy metalsin tweleve digested vegetables samples after neutralization. None of the non-spiked samplestested shows levels of heavy metals above the maximum residue limit (MRL) allowed forheavy metals in vegetables using both instrumental and papain assay. The papain assay wasable to detect by mercury-spiked vegetable samples indicating that the assay could tolerate thehigh salt of the digested sample matrix. Papain assay is simple, rapid and low in cost. It requiressmall sample volumes and could be carried out in a microplate format. The assay can act as apreliminary screening assay. Positive samples are sent for heavy metals level using instruments.Using this approach, higher frequency and number of monitoring can be carried out.
Keywords: heavy metals, vegetables, enzyme assay, FIMS